A comparison of single phase standalone square waveform solar inverter topologies: half bridge and full bridge - Aicha Chemseddine; Noureddine Benabadji; Ali Cheknane; Salah Eddine Mankour (International Journal of Electrical and Computer Engineering (IJECE), 2020)
In stand-alone photovoltaic installations the photovoltaic inverter allows transforming the DC power produced by the photovoltaic modules into an AC power. Depending on the shape of the AC output voltage generated by the inverter there exist three main types of stand-alone PV inverters: pure sine waveform inverters, modulated sine waveform inverters and square waveform inverters and each type of these inverters is also divided into different topologies. In this paper we will be interested and study the square waveform stand-alone inverter topologies which are the half bridge and the full-bridge inverter topologies.